Problems and Countermeasures in Copying of Medical Record of Traffic Accident Injury. (March 2014) - Wan, Xiaokang; Hong, Ying
Abstract In modern society, more and more people buy car insurance; therefore the copying of the medical record of traffic accident injury also becomes more common. However, the copying of the medical record of traffic accident injury is specific in situation. Laws and regulations on the copying situation are not clear, and people and insurance companies have insufficient knowledge of medical record copying, which poses many tricky copying needs for the staff responsible for the service and causes many copying disputes. The author analyzes the problems of copying the medical record traffic accident with respect to the responsible party and the injured party, identifies their reasons, and discusses the solutions and methods for solving such copying situations.